Composition of the diet of Netta peposaca (Birds: Anseriformes) in Santa Fe province, Argentina - Olguin, Pamela Fernanda (2014)
We examined the diet of the Rosy-billed Pochard, Netta peposaca (Vieillot, 1816), (n = 59) during the autumn of 2010 in Santa Fe province, Argentina. Were analyzed a total of 59 ducks (n = 37 females and n = 22 males) to assess their gastrointestinal contents. The trophic spectrum was composed of 16 taxa (plant fraction: animal fraction 9 and 7). The contribution of each food category estimated using the IRI was: Echynochloa sp. (Poaceae) = 4301, Polygonum sp. (Polygonaceae) = 956, and unidentified graminoid species = 53 (females: Echynochloa sp. = 4313, Polygonum sp. = 1095 and males: Echynochloa sp. = 5522, Polygonum sp. = 814). No significant differences were found between females and males in diet composition (Fisher's test, p < 0.05). Moreover, the diversity index (H') was significantly (Mann-Whitney, p < 0.05) different between sexes. The Rosy-billed Pochard showed a predominantly phytophagous feeding habit in autumn. Likewise, this is the first contribution on the sexual differences in the feeding biology of the Rosy-billed Pochard.